ENCOURAGING INFLUENCE IN THE MANAGEMENT OF INNOVATION AND PEDAGOGICAL ACTIVITIES - Rakhmanova E’zozkhon Yuldashevna (Web of Journals Publishing, 2025)
In the article the system of methods that provides the motivating impact in the management of innovative pedagogical activities is proposed. The author reveals integrative features of various combinations of the methods and possibilities of their application in the management of pedagogical innovations.
Keywords: innovative and pedagogical activities, motivating impact, methods of motivation, management of innovation.